2019
DOI: 10.3345/kjp.2018.06919
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlations in pediatric patients with myotonic dystrophy type 1

Abstract: Purpose Myotonic dystrophy, also known as dystrophia myotonica (DM), is an autosomal dominant disorder with 2 genetically distinct forms. DM type 1 (DM1) is the more common form and is caused by abnormal expansion of cytosine/thymine/guanine (CTG) repeats in the DM protein kinase ( DMPK ) gene. Our study aimed to determine whether the age of onset is correlated with CTG repeat length in a population of pediatric patients with DM1. Methods We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…In the current study CPK range in the LGMD group was (255-31219 IU/ L) with a mean of 10390. 2019), similar to our results, gender distribution was found to be 12 males (70.6 %) and 5 females (29.4 %) [18]. In contrast to that, according to a study done by Solbakken et al (2019), there were no significant differences in age or gender between the patients and the control group [19].…”
Section: Methodssupporting
confidence: 89%
“…In the current study CPK range in the LGMD group was (255-31219 IU/ L) with a mean of 10390. 2019), similar to our results, gender distribution was found to be 12 males (70.6 %) and 5 females (29.4 %) [18]. In contrast to that, according to a study done by Solbakken et al (2019), there were no significant differences in age or gender between the patients and the control group [19].…”
Section: Methodssupporting
confidence: 89%
“…We revealed that OR decreased by 27% with 1 week increase in gestational age, whereas OR increased by 31.27 with 1 unit increase in log 2 CTG repeat length, in other words, OR increased by 31.27 whenever the number of CTG repeat length doubled. The current clinical classi cation of DM1 is based on age at onset and CTG length [7,12,13,34,35]. On the other hand, several reports have shown no evidence of an effect of CTG repeat length on clinical severity [8,11,36].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for this nding is that the term CDM newborns had fewer CTG repeats (median: 1300) than preterm ones (median of 1900). Several studies have indicated the CTG repeat correlated with the disease phenotype [8,34,35]. Thus, having few CTG repeats with term CDM newborns induces a favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We revealed that OR decreased by 27% with 1 week increase in gestational age, whereas OR increased by 31.27 with 1 unit increase in log 2 CTG repeat length, in other words, OR increased by 31.27 whenever the number of CTG repeat length doubled. The current clinical classification of DM1 is based on age at onset and CTG length [ 7 , 12 , 13 , 34 , 35 ]. On the other hand, several reports have shown no evidence of an effect of CTG repeat length on clinical severity [ 8 , 11 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for this finding is that the term CDM newborns had fewer CTG repeats (median: 1300) than preterm ones (median of 1900). Several studies have indicated the CTG repeat correlated with the disease phenotype [ 8 , 34 , 35 ]. Thus, having few CTG repeats with term CDM newborns induces a favorable outcome.…”
Section: Discussionmentioning
confidence: 99%